Peasant-Based Societies in Chris Wickham’s Thought - Astarita, Carlos Alberto Tomas (2011)
This engagement with Chris Wickham’s Framing the Early Middle Ages argues that Germanic kings settled as political authorities in fiscal lands, and granted districts to some of the loyal members of their entourage over which they exercised power. This process relates to the fact that kings preserved fiscus-taxes, but that system had already deteriorated and finally disintegrated in the sixth century. In the long run, the problem was expressed in an organic crisis of the ruling class. In consequence, popular revolts against taxation ensued. These revolts are an indicator that the collapsed ancient machinery of domination was not replaced by another in the short term, thus giving way to a political vacuum. The fugitive slaves or serfs reflected in the laws are an indicator pointing in the same direction. Under these conditions free peasant-communities multiplied. These events take us to the concept of peasant-mode societies that Wickham contributes to our understanding of the period. Despite the importance he attaches to this concept, he observes nuances; not in all regions, he claims, did peasant-logic prevail. The evidence allows us, on the contrary, to extend the scope of the concept and to establish a single theoretical basis for the construction of the feudal system on a European scale.